Search for Pompe disease among patients with undetermined myopathies. (20th July 2015) - Lindberg, C.; Anderson, B.; Engvall, M.; Hult, M.; Oldfors, A.
Abstract : Objective: Pompe disease is a rare treatable glycogen storage disease with in adults ‐ a limb‐girdle muscle weakness. Muscle biopsy may fail to show the typical vacuolar myopathy. We asked if we had un‐diagnosed patients with Pompe disease in western Sweden. Material and Methods: We searched the muscle biopsy registry during the time period 1986 until 2006 including 3665 biopsies and included patients at our Neuromuscular Center with unspecified myopathy or limb‐girdle muscular dystrophy. The dry blood spot test was used to identify patients with Pompe disease. Results: A total of 82 patients (46 from the biopsy register and 36 from our center) were seen and dry blood spot test was obtained. No patient with Pompe disease was found. The dry blood spot test was low in three cases (11, 16, and 18% of normal) but a second blood sample showed a normal result based on GAA enzyme activity in lymphocytes in all three patients. In one patient with low normal result of the analysis in lymphocytes a genetic test showed no pathogenic mutations. Further investigation gave a definite diagnose of another myopathy in 12 patients. Conclusions: The prevalence of Pompe disease in western Sweden (3 in 1.27 million or 0.24 per 100.000 inhabitants) is lower than in the Netherlands and New York. Re‐evaluation of patients with myopathies but without definite diagnosis is rewarding since 12 of 82 patients in our study had a definite molecular diagnosis after workup.